An Analysis of the Implementation of Kurikulum Merdeka in Social Studies Learning at Elementary Schools - Rani, Apriza Rahma; Pebriana, Putri Hana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in Social Studies (IPS) learning at the elementary school level. The research focuses on planning, implementation, and evaluation processes aligned with the principles of differentiation and the strengthening of the Pancasila Student Profile. A qualitative descriptive approach was used, involving teachers and students from three public elementary schools. Data were collected through interviews, observations, and document analysis, then analyzed using data reduction, data display, and conclusion drawing techniques. The results show that teachers have attempted to implement the Merdeka Curriculum by adapting teaching tools and project-based learning methods. However, challenges remain in teachers’ understanding of formative assessment and the integration of contextual social values. Overall, the implementation of the Merdeka Curriculum in elementary school Social Studies has progressed well, although continuous guidance is needed to enhance innovation and authentic assessment practices.